2001
DOI: 10.1046/j.1528-1157.42.s6.7.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategy and Outcomes for Epileptic Patients with Focal Cortical Dysplasia or Dysembryoplastic Neuroepithelial Tumor

Abstract: Summary:  Purpose: The purpose of this study was to clarify and compare the influence of surgical strategy on relief from seizures in patients with focal cortical dysplasia (FCD) and those with dysembryoplastic neuroepithelial tumor (DNT). Methods: Six patients with FCD and five patients with DNT, all of whom underwent surgical resection for medically intractable epilepsy, were compared in terms of presurgical seizure types and frequency, location of lesions, magnetic resonance imaging (MRI), single‐photon em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…Patterns 1–3 were found in all patients injected during a partial seizure. Characteristic for these was hyperperfusion within and immediately surrounding the MRI‐visible FDL, consistent with intrinsic epileptogenicity of FDL (5,18) and confirming previous reports (11,19–21). These patterns followed a gradient of hyperperfusion in which the region with the maximum z score was either (i) at the lesion or its immediate surroundings (pattern 1), (ii) about 2 cm away from the lesion but connected to a second lobe of the hyperperfusion cluster at the lesion or its immediate surroundings through a propagation trail (pattern 2), or (iii) about 5 cm away from the lesion but connected to another hyperperfusion cluster at the lesion or its immediate surroundings through a propagation trail (pattern 3).…”
Section: Discussionsupporting
confidence: 89%
“…Patterns 1–3 were found in all patients injected during a partial seizure. Characteristic for these was hyperperfusion within and immediately surrounding the MRI‐visible FDL, consistent with intrinsic epileptogenicity of FDL (5,18) and confirming previous reports (11,19–21). These patterns followed a gradient of hyperperfusion in which the region with the maximum z score was either (i) at the lesion or its immediate surroundings (pattern 1), (ii) about 2 cm away from the lesion but connected to a second lobe of the hyperperfusion cluster at the lesion or its immediate surroundings through a propagation trail (pattern 2), or (iii) about 5 cm away from the lesion but connected to another hyperperfusion cluster at the lesion or its immediate surroundings through a propagation trail (pattern 3).…”
Section: Discussionsupporting
confidence: 89%
“…Because of their propensity for causing seizures despite optimal antiepileptic drug therapy, GG often require resection to achieve seizure control. Early resection reduces long‐term morbidity and mortality from seizures, making surgery the treatment of choice for most patients when compared to medical management (Silver et al, 1991; Kirkpatrick et al, 1993; Packer et al, 1994; Johnson et al, 1997; Morris et al, 1998; Jorge et al, 2000; Aronica et al, 2001a; Ildan et al, 2001; Kameyama et al, 2001; De Munnynck et al, 2002; Pasquier et al, 2002). A second concern for a small minority of patients with GGs, is that underlying the benign nature of these tumors lurks the potential for malignant transformation (Hayashi et al, 2001; De Munnynck et al, 2002; Whittle et al, 2002) especially within the glial component (Jay and Becker, 1994; David et al, 2000).…”
mentioning
confidence: 99%
“…Palmini et al reported that ictal or continuous epileptiform discharges (consisting of recruiting/derecruiting patterns, repetitive bursting patterns and (quasi)continuous rhythmic spiking) were related to cortical dysplasia (18). Since then, various reports on ECoG findings in cortical dysplasia have been published using different nomenclature and definitions, such as, slow repetitive spikes (37), rhythmic spike discharges (38), seizure patterns (consisting of continuous spiking, bursts of rhythmic spikes and trains of fast activity) (19), continuous epileptogenic discharges (25), frequent or continuous rhythmic spiking (39), and continuous frequent spiking (22). This difference in terminology makes direct comparison of these studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the clinical, neuroimaging, and histological characteristics of these indolent GNTs (21), but few(11,20,23,24,26,40–48) investigators have studied the ECoG spike discharge patterns of patients with a GNT, in contrast to those with FCD. Only a few studies report EEG and ECoG findings separately, and when they have, emphasis was mainly on the topography and distribution of the (inter) ictal discharge, and not on spike discharge patterns (11,25,26,40,48). For example, Raymond et al found that unequivocal spiking or sharp waves on the interictal scalp EEG were present in most patients with DNT but were concordant with the visible lesion in only three patients (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation